2019
DOI: 10.1128/jcm.01113-18
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis of the Diagnostic Accuracy of Nucleic Acid Amplification Tests for Tuberculous Meningitis

Abstract: The diagnosis of tuberculous meningitis (TBM) is difficult and poses a significant challenge to physicians worldwide. Recently, nucleic acid amplification (NAA) tests have shown promise for the diagnosis of TBM, although their performance has been variable. We undertook a systematic review and meta-analysis to evaluate the diagnostic accuracy of NAA tests with cerebrospinal fluid (CSF) samples against that of culture as the reference standard or a combined reference standard (CRS) for TBM. We searched the Emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 79 publications
1
32
0
Order By: Relevance
“…Given the limitations of tests for EPTB detection, Xpert MTB/RIF has been evaluated in several studies 9–15 . Although Xpert MTB/RIF assay has been validated for TB detection in sputum by authors in different countries, the efficacy of this automated molecular platform for TB detection in nonrespiratory specimens was highly variable, as its sensitivity ranged from 30% to 100% 1626 . Furthermore, the efficacy of Xpert MTB/RIF has not been yet investigated in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Given the limitations of tests for EPTB detection, Xpert MTB/RIF has been evaluated in several studies 9–15 . Although Xpert MTB/RIF assay has been validated for TB detection in sputum by authors in different countries, the efficacy of this automated molecular platform for TB detection in nonrespiratory specimens was highly variable, as its sensitivity ranged from 30% to 100% 1626 . Furthermore, the efficacy of Xpert MTB/RIF has not been yet investigated in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic accuracy of Xpert MTB/RIF for TBM has been evaluated in prior systematic reviews and meta‐analyses [54–58]. When Xpert MTB/RIF was evaluated in definite cases, the sensitivity ranged from 61 to 85% and specificity from 97% to 100% [54–58]. When Xpert MTB/RIF was evaluated versus a composite reference standard, the sensitivity ranged from 62.8% to 66% and specificity from 89% to 98.8% [54, 57].…”
Section: Discussionmentioning
confidence: 99%
“…When Xpert MTB/RIF was evaluated in definite cases, the sensitivity ranged from 61 to 85% and specificity from 97% to 100% [54–58]. When Xpert MTB/RIF was evaluated versus a composite reference standard, the sensitivity ranged from 62.8% to 66% and specificity from 89% to 98.8% [54, 57]. In most studies, CSF cultures were the gold standard; however, culture has only moderate sensitivity (30–60%) [59–61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negi et al reported sensitivities of Pab-PCR, BACTEC, LJ medium and ZN smear to be nearly 74, 53, 47 and 35 %, respectively, in 168 patients of suspected pulmonary and extra-pulmonary TB [15]. In a recently published systematic review, the pooled sensitivity and specificity of in-house nucleic acid amplification tests were 68 % (38-88 %) and 98 % (95-100 %), respectively [20]. The use of CSF 'filtrates' rather than 'sediments' may increase the sensitivity of PCR from 53-88 % [21].…”
Section: Discussionmentioning
confidence: 99%